Association of the components of ambient fine particulate matter (PM2.5) and chronic kidney disease prevalence in China. (1st August 2023) - Zhang, Xingyuan; Tao, Jiayi; Lei, Fang; Sun, Tao; Lin, Lijin; Huang, Xuewei; Zhang, Peng; Ji, Yan-Xiao; Cai, Jingjing; Zhang, Xiao-Jing; Li, Hongliang
Abstract: Previous research has implicated PM2.5 as a potential environmental risk factor for CKD, but little is known about the associations between its components and CKD. We conducted a nationwide cross-sectional study using the updated air pollution data in the nationwide population (N = 2, 938, 653). Using generalized additive models, we assessed the association between long-term exposure to PM2.5 and its components (i.e., black carbon [BC], organic matter [OM], nitrate [NO3 − ], ammonium [NH4 + ], sulfate [SO4 2− ]), and CKD prevalence. The air pollution data was estimated using high-resolution and high-quality spatiotemporal datasets of ground-level air pollutants in China. Besides, we adopted a novel quantile-based g-computation approach to assess the effect of a mixture of PM2.5 constituents on CKD prevalence. The average concentration of PM2.5 was 78.67 ± 22.5 μg/m 3, which far exceeded WHO AQG. In the fully adjusted generalized additive model, at a 10 km × 10 km spatial resolution, the ORs per IQR increase in previous 1-year average PM2.5 exposures was 1.380 (95%CI: 1.345–1.415), for NH4 + was 1.094 (95%CI: 1.062–1.126), for BC was 1.604 (95%CI: 1.563–1.646), for NO3 − was 1.094 (95%CI: 1.060–1.130), for SO4 2− was 1.239 (95%CI: 1.208–1.272), and for the OM was 1.387 (95%CI: 1.354–1.421), respectively. Subgroup analysis showed females, younger, and healthier were more vulnerable to this effect. In the further exploration of the joint effect of PM2.5 compositions (OR 1.234 [95%CI 1.222–1.246]) per quartile increase in all 5 PM2.5 components, we found that PM2.5 SO4 2− contributed the most. These findings provide important evidence for the positive relationship between long-term exposure to PM2.5 and its chemical constituents and CKD prevalence in a Chinese health check-up population, and identified PM2.5 SO4 2− has the highest contribution to this relationship. This study provides clinical and public health guidance for reducing specific air particle exposure for those at risk of CKD. Highlights: Long-term exposure to PM2.5 and its components is significantly associated with CKD prevalence. Sulfate is the strongest contributor to the CKD prevalence among PM2.5 components. Our research provids updated evidence for clinical and public health guidance.